Interactive Documentary : Adolescent Sexual Behavior The Impact Of It On Society And Themselves - Adzuan Izzudin Isma Zaki; Alia Abd Rahman (Journal of Computing Technologies and Creative Content, 2022)
Sex is an activity that is done by married couple for pleasure and or conceiving baby. But people nowadays also done it without being married and this included people aged as young as 13 years old. This documentary aims to find out why they are doing it at such young age. This study also aims to evaluate whether documentary is an effective medium in spreading awareness about the topic at hand. AGILE model was used for the research to ease the workflow